Model-Model Pembelajaran di Era 5.0 dan Tantangan dalam Implementasi - Muhammad Arifin; Noviyanti Noviyanti; Dedek Berliani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The Society 5.0 era demands that the world of education undergo various transformations, including the way teachers teach and students learn, the use of technology and creative learning approaches, and relevance to the real world. Transformation is accompanied by efforts to prepare human resources who are able to adapt, coexist and synergize with the use of technology. This study aims to identify and analyze learning models based on information and communication technology (ICT) that are relevant in supporting learning in the 5.0 era. The research method used is a literature study of various scientific sources, with a descriptive qualitative approach. Several learning models discussed include blended learning, flipped classroom, project-based learning, online-collaborative learning, game-based learning, and simulation-based learning. Each of these learning models has advantages in forming 21st century skills such as critical thinking, collaboration, creativity, and communication. However, in the implementation in the field, these models still face challenges such as the low level of teachers in implementing the model because they have never received training, limited technological infrastructure, and resistance to change. Therefore, the integration of ICT-based learning models requires the readiness of the education system as a whole to be able to realize effective, adaptive, and relevant learning in the digital era.